Ekstrak Enzim Protease Dari Daun Palado (Agave Angustifolia) Dan Pemanfaatannya Dalam Proses Pembuatan Virgin Coconut Oil - Male, Kasmir Sy.; Nuryanti, Siti; Rahmawati, Sitti (Jurnal Akademika Kimia, 2014)
Virgin coconut oil (VCO) can be made in several ways, namely through a heating process at low temperature, freeze-drying, fermentation, enzymatic, mechanical pressure or centrifugation. VCO with an enzymatic method is the making of VCO fromcoconut milk by using enzyme. The protein-oil bonds in the emulsions in coconut milk can be broken down into protease enzyme. The purpose of this research is to extract the protease enzyme in palado leaves and utilize the enzymes in the manufacturing process as well as determining the quality of VCO. This research method passed through some processes. Firstly enzyme extracts from palado leaves are prepared and coconut milk from coconut cream is made, then it is tested qualitatively the presence of protease enzyme with ninhydrin color reagent. Furthermore, the making of VCO enzymatically is undertaken by varying the ratio of the volume of coconut cream and enzyme extracts of 24 hours. VCO quality is analysis by using the parameters of smell, flavor, color, moisture content, levels of FFA (free fatty acid) and peroxide. The testing result with ninhydrin reagent gave a positive reaction (blue-purple) showing that there is enzymes alleged a class of protease in the palado leaf. The result of VCO made with the comparison of coconut cream and enzyme extracts from palado (10 : 1) has generate a VCO with a yield of 25.4%. However, from the analysis of VCO quality test results, it is obtained the smell of distinctive flavor oils, fragrance, the clean color, water content of 0.5% , FFA content of 0.25% and the peroxide number of 0 meq/kg.